Project Management and Performance of Rural Road Construction Projects in Machakos County, Kenya - Cornelius Wandiri; Rosemary James (European Scientific Journal, ESJ, 2020)
This paper explores the influence of project management practices on performance of rural road construction projects in Machakos County, Kenya. Rural road construction projects experience challenges that impede them from being successfully completed within the allocated cost budget, set timelines and to the desired quality. This study specifically investigated how project planning, project execution and project monitoring and control influence the performance of rural construction projects. The study conducted a census of all the 18 rural road construction projects in Machakos County by census. These projects were at various stages of completion. The number of respondents selected was 100 and in order to narrow down on these respondents, simple random sampling technique was used. The study used descriptive and causal research designs and applied a semi-structured questionnaire in collection of data. The study found out that project planning, project execution and project monitoring and control all had a positive and significant relationship with project performance. However, it was also found out that these project management practices were not being applied effectively in the road projects under study. The study concludes that project management practices greatly influence the performance of rural road construction projects. The study recommends that project management practices of project planning, project execution and project monitoring and control which form more than 85% of the project life cycle, should be effectively applied throughout the life cycle of implementing rural road construction projects in order to ensure that the projects meet the performance goals.